2016
DOI: 10.1016/j.ntt.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of C. elegans eggs to a glyphosate-containing herbicide leads to abnormal neuronal morphology

Abstract: Recent data demonstrate that chronic exposure of Caenorhabditis elegans (C. elegans) to a high-use glyphosate-containing herbicide, Touchdown (TD), potentially damages the adult nervous system. It is unknown, however, whether unhatched worms exposed to TD during the egg stage show abnormal neurodevelopment post-hatching. Therefore, we investigated whether early treatment with TD leads to aberrant neuronal or neurite development in C. elegans. Studies were completed in three different worm strains with green fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 53 publications
0
12
0
1
Order By: Relevance
“…It has also been shown to serve as a source of phosphorous for algae at low concentrations (Klátyik et al, 2017b;Wang et al, 2017), and therefore, to potentially induce algal bloom (Drzyzga and Lipok, 2017). Formulated glyphosate-based herbicides, Touchdown R and Roundup R caused neurotoxicity (McVey et al, 2016) as well as locomotion and fertility inhibition (García-Espiñeira et al, 2018) on the nematode Caenorhabditis elegans. Following the results of the late Andrés Carrasco and his research group (Paganelli et al, 2010;Carrasco, 2013), recent findings in environmental toxicology of glyphosate and its formulated products include its revealed toxicity on amphibian species (Mann et al, 2009;Relyea and Jones, 2009;Meza-Joya et al, 2013;Wagner et al, 2013;Henao Muñoz et al, 2015;Baier et al, 2016a,b), on mollusks (Conners and Black, 2004) and on earthworms (Zaller et al, 2014;Gaupp-Berghausen et al, 2015).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…It has also been shown to serve as a source of phosphorous for algae at low concentrations (Klátyik et al, 2017b;Wang et al, 2017), and therefore, to potentially induce algal bloom (Drzyzga and Lipok, 2017). Formulated glyphosate-based herbicides, Touchdown R and Roundup R caused neurotoxicity (McVey et al, 2016) as well as locomotion and fertility inhibition (García-Espiñeira et al, 2018) on the nematode Caenorhabditis elegans. Following the results of the late Andrés Carrasco and his research group (Paganelli et al, 2010;Carrasco, 2013), recent findings in environmental toxicology of glyphosate and its formulated products include its revealed toxicity on amphibian species (Mann et al, 2009;Relyea and Jones, 2009;Meza-Joya et al, 2013;Wagner et al, 2013;Henao Muñoz et al, 2015;Baier et al, 2016a,b), on mollusks (Conners and Black, 2004) and on earthworms (Zaller et al, 2014;Gaupp-Berghausen et al, 2015).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…Additionally, C. elegans has a transparent body that makes microscopic imaging of tissues and labeled proteins much easier than in mammals. For example, C. elegans expressing GFP-tagged neuronal populations (pan, dopaminergic, or GABAergic) were exposed to the herbicide glyphosate and the effect upon specific populations of neurons was determined 17 . In this study, dopaminergic neurons were more sensitive than GABAergic neurons to glyphosate exposure.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, current emerging evidence suggests that glyphosate or GBH such as Roundup, can adversely affect mammalian biology via multiple mechanisms 5 8 . Several studies have also suggested the possible link between GBHs exposure and abnormality in neurodevelopment 9 , 10 . Among those mechanisms, it has been reported that GBHs exposure can alter the microbiota in honeybees, rats and other animals 11 , 12 and recently a shotgun metagenomic approach revealed that glyphosate alters the gut microbiome of Sprague–Dawley (SD) rats by inhibiting the shikimate pathway 13 .…”
Section: Introductionmentioning
confidence: 99%